Advances in Takayasu arteritis: An Asia Pacific perspective - Danda, Debashish; Manikuppam, Prathyusha; Tian, Xinping; Harigai, Masayoshi (Frontiers in Medicine, 2022)
Takayasu Arteritis (TA) is a rare form of chronic granulomatous large vessel vasculitis that is more common in Asia compared to other parts of the world. There have been several developments in the field of Takayasu arteritis in relation to genetics, classification, clinical features, imaging, disease activity assessment and management and much of these works have been done in the Asia Pacific region. We will be discussing selected few in the current review.